Impact of Hypertension on Cognitive Function: A Scientific Statement From the American Heart Association - Iadecola, Costantino; Yaffe, Kristine; Biller, José; Bratzke, Lisa C; Faraci, Frank M; Gorelick, Philip B; Gulati, Martha; Kamel, Hooman; Knopman, David S; Launer, Lenore J; Saczynski, Jane S; Seshadri, Sudha; et al. (Hypertension (Dallas, Tex. 1979), 2016)
Age-related dementia, most commonly caused by Alzheimer disease or cerebrovascular factors (vascular dementia), is a major public health threat. Chronic arterial hypertension is a well-established risk factor for both types of dementia, but the link between hypertension and its treatment and cognition remains poorly understood. In this scientific statement, a multidisciplinary team of experts examines the impact of hypertension on cognition to assess the state of the knowledge, to identify gaps, and to provide future directions. Authors with relevant expertise were selected to contribute to this statement in accordance with the American Heart Association conflict-of-interest management policy. Panel members were assigned topics relevant to their areas of expertise, reviewed the literature, and summarized the available data. Hypertension disrupts the structure and function of cerebral blood vessels, leads to ischemic damage of white matter regions critical for cognitive function, and may promote Alzheimer pathology. There is strong evidence of a deleterious influence of midlife hypertension on late-life cognitive function, but the cognitive impact of late-life hypertension is less clear. Observational studies demonstrated a cumulative effect of hypertension on cerebrovascular damage, but evidence from clinical trials that antihypertensive treatment improves cognition is not conclusive. After carefully reviewing the literature, the group concluded that there were insufficient data to make evidence-based recommendations. However, judicious treatment of hypertension, taking into account goals of care and individual characteristics (eg, age and comorbidities), seems justified to safeguard vascular health and, as a consequence, brain health.